Working with Excel: Refreshing Math Skills for Management - Chaffe-Stengel, Priscilla (Business Expert Press, 2012)
Ebook from IG Library ; Managers and analysts routinely collect and examine key performance measures to better understand their operations and make good decisions. Being able to render the complexity of operations data into a coherent account of significant events requires an understanding of how to work well in the electronic environment with raw data. Although some statistical and financial techniques for analyzing data are sophisticated and require specialized expertise, there are methods that are understandable and applicable by anyone with basic algebra skills and the support of a spreadsheet package. While specialized software packages may be used in a particular business setting, Microsoft Excel is routinely available on computer desktops. Managers who have been in the field any length of time may not be sufficiently familiar with the capabilities of Excel to make optimal use of its functionalities. Prior to undertaking a program to pursue executive training, managers who are refreshed with basic algebra skills and the capabilities of Excel will be prepared to develop a richer understanding from their more advanced work. The primary foci of this text are (1) to refresh fundamental mathematical operations that broadly support statistical and financial equations and formulas, (2) to introduce work with equations and formulas in Excel spreadsheets, (3) to expand statistical and financial analysis with the programmed Excel functions readily available through the 'Insert Function' toolbar button and the more advanced Data Analysis Toolkit, (4) to facilitate graphic representations of data, and finally (5) to prepare data mounted in differing file formats. This text is a companion to a series of books that addresses the analysis of sample data, time series data, managerial economics, and forecasting techniques. Together these books will equip the manager and the student with a solid understanding of applied data analysis and prepare them to apply the methods themselves.